The New Partnership for Africa's Development: implications for the realisation of socio-economic rights in Africa - Mbazira, Christopher (Economic and Social Rights in South Africa, 2004)
The New Partnership for Africa's Development : Implications for the realisation of socio-economic rights in Africa Christopher Mbazira The realisation of socio-economic rights in Africa remains a distant goal. The majority of Africans live in poverty. Chronic hunger, malnutrition, HIV/Aids, ignorance and illiteracy continue to plague the continent. Military dictatorships, poor leadership, corruption, political conflicts, globalisation and structural adjustment programmes (SAPs) have all contributed to this situation. The debt burden exceeds manageable levels. States have increasingly withdrawn from providing such essential services as education, electricity and health.